(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
In recent years, the integration of educational games into the learning environment has gained widespread recognition as a dynamic teaching strategy. This research article explores the major benefits of incorporating educational games into instruction, highlighting how they enhance student engagement, motivation, knowledge retention, collaborative skills, and problem-solving abilities. Drawing from contemporary studies and classroom observations, this paper aims to present a compelling case for the systematic use of educational games in modern education.